2020
DOI: 10.36095/banxico/di.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Automation Technologies and Employment at Risk: The Case of Mexico

Abstract: Based on the methodology proposed by Frey and Osborne (2017), we use their estimates for the probability of automation of occupations together with household survey data on the occupational distribution of employment to provide a risk assessment for the threat that automation may pose to the Mexican labor market. We find that almost two thirds of total employment is at high risk of automation; slightly more than half if we only consider employment in the formal sector. We argue that, while these estimates prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…They explain that routine jobs are the ones which are more exposed to digitalization, that is, jobs which follow well-defined procedures, since they can be easily carried out by computer systems. Cebreros et al (2020) for example, suggested a list of occupations which could be easily automatized, including tax accountants, library technicians, customs specialists, mathematical technicians, telemarketers, insurance sellers, catalogue sellers and tailors. They estimated that 65 per cent of employment and 57 per cent of formal employment in Mexico is at high risk of being digitized and that less experienced (younger) and less educated workers are the ones who could be more subjected to displacement by technology.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…They explain that routine jobs are the ones which are more exposed to digitalization, that is, jobs which follow well-defined procedures, since they can be easily carried out by computer systems. Cebreros et al (2020) for example, suggested a list of occupations which could be easily automatized, including tax accountants, library technicians, customs specialists, mathematical technicians, telemarketers, insurance sellers, catalogue sellers and tailors. They estimated that 65 per cent of employment and 57 per cent of formal employment in Mexico is at high risk of being digitized and that less experienced (younger) and less educated workers are the ones who could be more subjected to displacement by technology.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…creation of new tasks). See, for example, Autor and Salomons (2018) for the case of 18 Organization for Economic Cooperation and Development (OECD) countries over the 1970-2008Acemoglu and Restrepo (2018) and Acemoglu and Restrepo (2019) for the case of the US over the 1993-2014period and the 1947Acemoglu et al (2020) for the case of France over the -2015and Cebreros et al (2020) for the case of Mexico over the 2016-2017 period.…”
Section: The Effect Of Technological Change On Labor Marketsmentioning
confidence: 99%
“…First, it simultaneously investigates both the effect of trade and technology on labor market aggregates, and not just the impact of one or the other as it has been the case up until now (e.g. Mendez, 2015;Chiquiar et al, 2017;and Cebreros et al, 2020). In addition, the estimated empirical specification includes both a measure of exposure to rising Chinese import competition in the US market and a measure of NAFTA integration in order to assess which is more important in understanding labor market outcomes.…”
Section: Introductionmentioning
confidence: 99%